Non-English Students’ Difficulties and Challenges in Learning Vocabulary - wahyu tri utami (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT: This study aims to investigate the problems faced by students in majoring in Indonesian language and literature education of third semester at University of Islam Malang in vocabulary and their strategies used by students to solve their problems in vocabulary majoring in Indonesian language and literature education of third semester at University of Islam Malang .The research problems were formulated as follows:(1) what are problems faced by non English students in vocabulary? (2) What are the strategies used by non-English students in vocabulary?This research belongs to descriptive qualitative research. The researcher took one student who got highest score in vocabulary test, one student who got lowest score in vocabulary test. They came from third semester Indonesian language and literature education major Indonesian language and literature education major. Interview guide consisting to 7 items related to problems and strategies. The data were analyzed in the form of descriptive qualitative analysis through by using coding, display data, and drawing conclusion by narrating the information taken from the interview guide for students.The findings of the study that the problems faced by English students from third semester in Indonesian language and literature education major of University of Islam Malang were same .The mainly found problems in difficult find new vocabulary collected in memory, difficult in writing and memorizing of vocabularies in activity class .And then the researcher also found strategies used as solution for the their problems including memory strategies and cognitive strategies.Therefore, future researcher is suggested to find new great strategies to help students face to problems especially in vocabulary by using more than one instrument and involve more than two participants with different level by means of providing better generalization. In addition, it is worth to recommend that more detailed issues related to the students’ problems and strategies to solve problem in vocabulary are discussed in the next research. Keywords : Difficulties challenges, learning strategies, and learning vocabulary